Religion Welcome Here: A Pluriversal Approach to Religion and Global Bioethics - Jecker, N.S.; Atuire, C.A.; Ravitsky, V.; Ghaly, M.; Vaswani, V.; Voo, T.C. (Bioethical Inquiry, 2024)
This paper sets forth and defends a pluriversal approach to religion in the context of an increasingly global bioethics. Section I introduces a pluriversal view as a normative technique for engaging across difference. A normative pluriversal approach sets five constraints: civility, change from within, justice, non-domination, and tolerance. Section II applies a a pluriversal approach to religion. It argues that this approach is epistemically just, recognizes diverse standpoints, and represents a productive, preferred, way to tackle global bioethics concerns. Section II also considers an opposing viewpoint, which holds that religious perspectives have no place in bioethics. We show that this viewpoint would have adverse effects on bioethics publishing, conferencing, and training programmes. The paper concludes (in Section III) that bioethicists should engage with people who hold different worldviews, including religious worldviews, and should do so in accordance with pluriversal ethical constraints.
Research Article
Keywords: Pluriversal view; Religion; Global bioethics; Epistemic justice; Public reason